UTERINE LEIOMYOSARCOMA: About 13 Cases and Review of the Literature - FZ, TERRAB; F., ALLOUCH; S., GHAMAD; T., BOUHAFA; Z., ALAMI; K., HASSOUNI (Journal of Medical Biomedical and Applied Sciences, 2018)
The uterine leiomyosarcoma (LMS) is a rare cancer arising from the smooth myometrial cells. The LMS is clinicallyaggressive malignancy, accounting for 2% to 6% of uterine malignancies and a very low annual incidence.Object of the study: To evaluate management and outcome of the treatment of uterine leiomyosarcoma.Patients and methods: Retrospective study of a series of 13 patients treated for uterine leiomyosarcoma in thedepartment of radiotherapy of CHU Hassan II, Fes between 2012 and 2016Results: The condition is rarely suspected preoperatively, diagnosis is usually made on histological examination ofthe operative specimen. The outcome is related to the mitotic activity of the tumour and to the infiltration of nearlystructures. Surgery is the only effective treatment, chemotherapy is ineffective, adjuvant radiotherapy improves localcontrol of the tumour but has no incidence on survival.Conclusion: In the absence of an effective adjuvant treatment, uterine leiomyosarcoma bears a poor prognosis withthe only exception of small non infiltring tumours with a low mitotic activity.